Correlations of the cladode area index with morphogenetic and yield traits of cactus forage - Pinheiro, Karina Mendes; Silva, Thieres George Freire da; Carvalho, Herica Fernanda de Sousa; Santos, Jannaylton Everton Oliveira; Morais, José Edson Florentino de; Zolnier, Sérgio; Santos, Djalma Cordeiro dos (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this work was to evaluate the correlations of the cladode area index with morphogenetic and yield traits of the cactus forage (Nopalea sp. and Opuntia sp.). Three clones of cactus forage were evaluated in dry land conditions: IPA Sertânia, Miúda, and Orelha de Elefante Mexicana. Morphological data from cladode and plant, cladode area index, and accumulated dry biomass were obtained at harvest. The relationship between the collected data was analyzed by path analysis, after the application of Pearson’s correlation matrix and the multicollinearity test. Higher correlations of morphogenetic traits were observed with crop yield than with the cladode area index, with R2 between 0.5930 and 0.9502. The variables height x width and total number of cladodes were the ones that best explained the variation of the cladode area index. The total number of cladodes, the cladode area index, and the morphology of fourth‑order cladodes are the variables that best explain the yield variability of the cactus forage clones evaluated in semiarid environment.